The Evil: Dowry System in India - Ranjan, Shivangi (Archives of Community Medicine and Public Health, 2024)
This article examines the dowry system in India, tracing its origins from ancient customs like 'Kanyadan' and 'Stridhan' to its current form as a harmful social practice. Initially acts of generosity, these traditions have evolved into compulsory and often abusive expectations, causing immense suffering for many women. The article explores the dowry system's persistence in modern society and the legal measures designed to combat it, highlighting the challenges of enforcement due to entrenched societal attitudes and a sluggish judicial system. The focus is not solely on identifying the problem but also on proposing solutions. It advocates for a holistic approach, including education, financial empowerment of women, raising awareness about legal rights, and public campaigns to shift cultural norms. The goal is to foster a culture of gender equality and create a supportive environment for those affected by dowry-related violence. Communities are urged to actively participate in this fight, supporting a more equitable society for women. By examining recent statistics and events, the article emphasizes the urgent need to address the dowry system directly. It calls for collective action to work towards eradicating this practice and achieving a future where dowry is a thing of the past.